Entre désir de nature et peur de l’abandon : quelles attentes paysagères après l’arasement des barrages hydroélectriques de la Sélune ? - Marie-Anne Germaine; Ludovic Drapier; Laurent Lespez; Marie-Jo Menozzi; Olivier Thomas (Projets de Paysage)
Through the example of a project for the removal of two hydroelectric dams of 16 and 36 metres in height spanning the Sélune River, this article examines the importance of the landscape in such a project and in the discussions concerning its implementation. The removal of obstacles spanning a river leads to a major reconfiguration of river environments and landscapes. The restoration of the river ecosystems involves defining new landscapes and at the same time this process is hampered by the great variety of representations of the stakeholders and by their different profiles. The aim is to see how the variety of views regarding the landscape can be crucial in addressing resistance to the ecological restoration of watercourses. This article is based on a confrontation of the representations of landscapes by residents and users in a survey, administered as part of a participant observation process, which involved qualitative interviews, implicit proposals made by the people promoting the levelling of the dams, and the concrete landscape project proposals made by design offices. The comparison of the landscape projects presented by the experts and the expectations expressed by the inhabitants pleads in favour of finding ways of more effectively taking the landscape into account. Since dismantling such structures results in the generation of new landscapes and raises the question of choices for the development of the dewatered areas, it seems necessary to take into consideration the expectations of local populations.